Proteomic Profiling of Iron‐Treated Ovarian Cells Identifies AKT Activation that Modulates the CLEAR Network. Issue 23 (30th October 2018) - Rockfield, Stephanie; Guergues, Jennifer; Rehman, Nabila; Smith, Aaron; Bauckman, Kyle A.; Stevens, Stanley M.; Nanjundan, Meera
Abstract: Although iron is essential for cell survival, dysregulated levels can contribute to cancer development or even cell death. The underlying mechanisms mediating these events remain unclear. Herein, proteomic alterations are assessed in iron‐treated ovarian cell lines using reverse phase protein array (RPPA) technology and potential functional responses via ingenuity pathway analysis (IPA). Using these approaches, upregulation of pathways modulating organismal death with alterations in mTOR, MAPK, and AKT signaling in HEY ovarian cancer cells in contrast to T80 non‐malignant ovarian cells is noted. Since modulation of cell death is mediated in part via microphthalmia‐associated transcription factor (MiTF) family, which regulates lysosomal biogenesis and autophagosome formation by upregulating expression of coordinated lysosomal expression and regulation (CLEAR) network, expression changes in these factors in response to iron are investigated. Increased transcription factor EB (TFEB) in T80 (relative to HEY), accompanied by its nuclear translocation and increased CLEAR network gene expression with iron, is identified. Inhibition of AKT alters these responses in contrast to mTOR inhibition, which has little effect. Collectively, these findings support use of RPPA/IPA technology to predict functional responses to iron and further implicate AKT pathway and MiTF members in iron‐induced cellular responses in ovarian cells.